2019
DOI: 10.1038/s41467-019-10854-1
|View full text |Cite
|
Sign up to set email alerts
|

Manganese acting as a high-performance heterogeneous electrocatalyst in carbon dioxide reduction

Abstract: Developing highly efficient electrocatalysts based on cheap and earth-abundant metals for CO 2 reduction is of great importance. Here we demonstrate that the electrocatalytic activity of manganese-based heterogeneous catalyst can be significantly improved through halogen and nitrogen dual-coordination to modulate the electronic structure of manganese atom. Such an electrocatalyst for CO 2 reduction exhibits a maximum CO faradaic efficiency of 97% and high current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
239
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(248 citation statements)
references
References 50 publications
9
239
0
Order By: Relevance
“…Other transition metal‐based SACs have also been developed for the CO 2 RR including ZnN 4 and MnN 4 Cl sites. Zhang et al demonstrated that the CO 2 RR activity of the MnN 4 moiety could be significantly improved through the introduction of external Cl ligands ( Figure 14 ).…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
See 2 more Smart Citations
“…Other transition metal‐based SACs have also been developed for the CO 2 RR including ZnN 4 and MnN 4 Cl sites. Zhang et al demonstrated that the CO 2 RR activity of the MnN 4 moiety could be significantly improved through the introduction of external Cl ligands ( Figure 14 ).…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…Zhang et al demonstrated that the CO 2 RR activity of the MnN 4 moiety could be significantly improved through the introduction of external Cl ligands ( Figure 14 ). Cl‐coordinated MnN 4 ((Cl, N)‐Mn/G) was synthesized by the pyrolysis of MnCl 2 and ethylenediamine at 800 °C and the Cl‐free control sample (N‐Mn/G) was obtained by using Mn(NO 3 ) 2 as the precursor. The (Cl, N)‐Mn/G exhibited a higher CO 2 RR activity than N‐Mn/G with a maximum CO FE of 97% and a low overpotential of 0.49 V at 10 mA cm −2 (Figure b–d).…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
See 1 more Smart Citation
“…From the XPS data in Table S2 (Supporting Information), the N/C ratio for samples in the Fe 1 NC/S 1 -Y series is inversely proportional to the thermal activation temperature, which is in sharp contrast to the proportional correlation between the CO 2 ER activity of Fe 1 NC/S 1 -Y series and thermal activation temperature Figure 3. a) FE CO and b) J CO of Fe 1 NC/S 1 -Y series and NC/S 1 -1000. c) FE CO of Fe 1 NC/S 1 -1000, highlighted by the shaded region, compared to that of other reported state-of-the-art nonprecious metal/N-doped carbon-based SACs with FE CO over 90%: Fe-N 5 , [28] Fe-N-C, [29] Co-N 2 , [30] Ni-NG, [31] NiN-GS, [32] Ni-N-Gr, [33] A-Ni-NSG, [34] Co-N 5 /HNPCSs, [35] COF-367-Co, [36] ZnN x /C, [37] (Cl,N)-Mn/G, [38] and AD-Sn/N-C 1000. [26] d) TOFs of Fe 1 NC/S 1 -1000 compared to that of other reported nonprecious metal/N-doped carbon-based SACs: Fe-N-C, [29] Fe 3+ -N-C, [25] Fe-N 5 , [28] Fe 0.5 d, [39] Co-N 2 , [30] A-Ni-NSG, [34] AD-Sn/N-C, [26] and Co-N 5 /HNPCSs.…”
Section: Gas Diffusion Strategy For Inserting Atomic Iron Sites Into mentioning
confidence: 99%
“…For the formation of CO, four‐nitrogen‐anchored Zn single atom is reported to display a low overpotential down to 24 mV and a FE up to 95% at −0.43 V due to the decreased free energy barrier of the formation of *COOH on Zn‐N 4 sites. [ 100 ] Very recently, Zhang et al developed halogen and nitrogen dual‐coordinated single Mn atom for ECR with a CO FE of 97% and current density of around 10 mA cm −2 at a low overpotential of 0.49 V. [ 101 ] Meanwhile, the (Cl, N)‐Mn/G catalyst exhibited an extremely high TOF of 38 347 h −1 at the overpotential of 0.49 V. The currently developed SACs mostly reduce CO 2 into formate and CO with high FEs over 90%, while the production of hydrocarbons is relatively difficult. Cu metal has been reported to be more active for hydrocarbon production than other metals.…”
Section: Modifying the Nanostructured Electrocatalysts At Atomic Scalmentioning
confidence: 99%